PENGARUH DIMENSI KUALITAS LAYANAN TERHADAP KEPUASAN DAN LOYALITAS NASABAH TABUNGAN SINAR PADA PT. BANK RIAU KEPRI CABANG TELUK KUANTAN - Wahyudi. M, Juju Eka; Restuti, Sri (Jurnal Tepak Manajemen Bisnis, 2015)
This study aims to analyze the influence of the dimensions of quality of the service whichconsists of Tangible (direct evidence), Empathy, Responsiveness (responsiveness), Reliability(reliability), Assurance (collateral) for customer satisfaction and loyalty SINAR saving at PT. BankRiau Kepri Branch Teluk Kuantan. The method used in this research is descriptive and path analysis,primary data collection through a questionnaire to 153 people, supported by analysis of primary andsecondary data through questionnaires, interviews and data agencies related to the problem understudy.The results show, that tangible, empathy, reliability, responsiveness and assurance have a significantdirect effect and positive impact on satisfaction. tangible, empathy, reliability, responsiveness andassurance have a significant direct effect and positive impact on loyalty, and satisfaction has a directinfluence a significant and positive impact on loyalty.In this study the authors suggest to the company in order to continuously improve the reliability ofcreating customer satisfaction and better care for each customer so that customer loyalty is maintained.The author also suggests that companies still perform periodic measurements of satisfaction levels.Keywords: Service Quality, Satisfaction and Loyalty.